ANALISIS KEBUTUHAN PENGGUNAAN BAHASA INGGRIS MELALUI IKLAN LOWONGAN PEKERJAAN DI MEDIA CETAK - Siti Yuliah; Krisna Yudha Bakhti; Dedy Setiawan (Jurnal Bahasa Inggris Terapan, 2016)
The present research is analysing job ads to find out the jobs that require English skills and other skills apart from English language. The job ads analysed were those that appeared on well-known Indonesian newspapers which were published in the periods of May, June and July 2016. The research found that all of the four language skills were required in the world of work, the emphasis, however, is put on active language skills such as speaking and writing. The present research also suggest that most of all professional position especially of administrative officers require their applicants to have English skills.Computer skill as well as communication skill have become the main supporting skills in applying for jobs. Despite the fact that  they are all Indonesian newspapers using Indonesian as the main language, a number of ads were written in English. Although such a proportion is still below the number of ads written in Indonesian, those English language ads show us how important English is to the applicants.   Keywords:job ads, English skills, applicants